Evaluating the intestinal immunity of Asian Seabass (Lates calcarifer, bloch 1790) following field vaccination using a feed-based oral vaccine - Raju, Thanusha; Manchanayake, Tilusha; Danial, Amir; Zamri-Saad, Mohd; Azmai, Mohammad Noor Amal; Md Yasin, Ina Salwany; Mohd Nor, Norhariani; Salleh, Annas (Multidisciplinary Digital Publishing Institute, 2023)
This study describes the levels of gut lysozyme and IgM, the number, size and density of gut-associated lymphoid tissue (GALT) regions, and the lymphocyte population in Asian seabass following field oral administration of a feed-based vaccine. Fish in a grow-out farm were selected and divided into two groups; Group 1 was vaccinated at week 0, 2, and 6, while Group 2 was not vaccinated. Samplings were done at 2-week intervals when the fish were observed for clinical signs, and gross lesions were recorded. The intestinal tissue and gut lavage fluid were collected. GALT regions (numbers, size, density and population of lymphocytes) were analyzed. Clinical signs such as abnormal swimming pattern and death, and gross lesions including scale loss, ocular opacity, and skin ulceration were observed in both groups. At the end of the study, the incidence rate between both groups were significantly different (p < 0.05). The gut IgM level and lysozyme activity, lymphocyte population, number, size and density of GALT regions of Group 1 were significantly (p < 0.05) higher than Group 2. Therefore, this study concludes that the feed-based vaccine reduces the incidence of vibriosis by stimulating the gut immunity of the vaccinated fish with an enhanced GALT region, specific IgM production against Vibrio harveyi, and lysozyme responses.